Resonance elliptic variational inequalities with discontinuous nonlinearities of linear growth - Pavlenko, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We consider resonance elliptic variational inequalities with second-order differential operators and discontinuous nonlinearity of linear grows. The theorem on the existence of a strong solution is obtained. The initial problem is reduced to the problem of the existence of a fixed point in a compact multivalued mapping and then, with the use of the Leray - Schauder method, the existence of the fixed point is established.